Mathematical problem-solving: The impact of personality type on the system of linear equations in two variables - Tiana, Hisna; Purwanto, Sigid Edy (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to justify students' mathematical problem-solving abilities on the material of the System of Linear Equations in Two Variables in terms of the Hippocrates-Galenus personality type. This research method is included in qualitative descriptive research. The technique used is purposive sampling. The instruments in this research were personality-type questionnaires, mathematical problem-solving ability tests, and interviews. The triangulation technique was obtained by comparing the results of the student's problem-solving ability tests on the material of the System of Linear Equations in Two Variables with the results of the interviews. The results of this research are that the sanguine did not fulfill the aspect of re-examining all the stages that have been carried out, the choleric did not meet the problem-identifying aspect, the melancholy fulfilled the four aspects of mathematical problem-solving, and the phlegmatic did not meet two aspects, namely solving the problem according to the plan and re-examining all the stages that have been completed. Each student with each personality type according to Hippocrates-Galenus has different thoughts and steps to solve mathematical problems, therefore both educators and students who have different mindsets are expected to understand different thoughts.